Kearifan Lokal dan Islam Moderat sebagai Fondasi Keadilan Pidana dalam KUHP Baru - Haniyah, Haniyah; Ramadhani, Muhammad Fadhil (Proceedings of Annual Conference for Muslim Scholars, 2025)
Criminal law reform through the ratification of the new Criminal Code is an important milestone in the journey of national law reform. These changes do not only concern the legal-formal aspect, but also demand adjustment to the social and cultural values that live in society. In the pluralistic context of Indonesia, the enforcement of justice cannot be separated from local wisdom and moderate religious values. This research aims to examine how local wisdom and moderate Islamic principles can be integrated as the basis for the formation of criminal justice in the new Criminal Code. The method used is normative-juridical legal research with a legislative, conceptual, and value approach. The results of the study show that the new Criminal Code recognizes living law, which is a law that grows from social practices, customs, and community beliefs. Local wisdom emphasizes the value of deliberation, balance, and the restoration of social relations, while moderate Islam prioritizes tolerance, balanced justice, and compassion in the legal process. The integration of the two opens up opportunities for criminal law reform that is more adaptive to social change, as well as affirming the role of law as a means of building harmony and strengthening human values in a diverse society.